Application of diffusion dialysis for reduction of acidity of real pregnant leach solutions containing Ni and Co ions. Issue 12 (12th August 2020) - Janiszewska, Małgorzata; Arguillarena, Andrea; Wajs, Magdalena; Staszak, Katarzyna; Regel-Rosocka, Magdalena
ABSTRACT: Diffusion dialysis (DD) was proposed as a pretreatment step to reduce the acidity of real sulfate/chloride pregnant leach solutions containing cobalt(II) and nickel(II). Optimum DD conditions that enable reduction of acidity in the feed while maintaining a high rejection level of metal ions present in PLS were proposed, e.g . for 0.06 dm 3 /min flow of both aqueous phases H + concentration in the dialysate reached 3.8 and 2.99 M for PLS1 and PLS2, respectively. Acid diffusion coefficients varied from 0.32∙10 −6 to 3.15∙10 −6 m/s and decreased with increasing phase flow rates. Moreover, dialysate neutralization was beneficial for the H + reduction in the feed.